Positionality and collaboration during fieldwork:insights from research with co-nationals living abroad - Chereni, Admire (Institut für Qualitative Forschung, 2017)
The researcher is a primary instrument in qualitative research. He/she is the key person in facilitating conversations during fieldwork and in making sense of the data. Methodological literature underscores the fact that assuming insider positions or identities during fieldwork aids qualitative researchers in achieving genuine collaboration, which is necessary for collecting trustworthy data. Furthermore, the contingency nature of positionality has been acknowledged sufficiently in literature: whilst the researcher positions himself or herself, he or she is simultaneously positioned by participants. Despite these insights, the manner in which the researchers' identities unfold during fieldwork interactions has attracted little attention in social science scholarship. Detailed accounts of how the researcher might influence the processes of positionality in order to engage participants in a productive collaboration are few. How might the researcher influence his or her positionality to meet the demands of collecting trustworthy data? In this article, I draw on a qualitative study of Zimbabweans in Johannesburg to reflect on how researchers can potentially negotiate, enact, and perform identities within unique relational spaces of fieldwork in order to achieve useful collaboration.